Clinical Efficacy of a Single Two Gram Dose of Azithromycin Extended Release for Male Patients with Urethritis - Satoshi Takahashi; Hiroshi Kiyota; Shin Ito; Akihiko Iwasawa; Yoshiki Hiyama; Teruhisa Uehara; Koji Ichihara; Jiro Hashimoto; Naoya Masumori; Kenichi Sunaoshi; Koichi Takeda; Nobukazu Suzuki; et al. (MDPI AG, 2014)
To clarify the clinical efficacy of a single oral 2 g dose of azithromycin extended-release for heterosexual male patients with urethritis, and the current antimicrobial sensitivity of Neisseria gonorrhoeae to azithromycin, a prospective clinical trial was conducted from 2011-2013. In patients with gonococcal urethritis, the eradication rate was 90.9% (30 of 33). The susceptibility rates of isolated Neisseria gonorrhoeae strains to ceftriaxone, spectinomycin, cefixime and azithromycin were 100%, 100%, 95.3% (41/43) and 37.2% (16/43), respectively. In the patients with nongonococcal urethritis, the eradication rate was 90.0% (45 of 50). The microbiological eradication rates for the pathogens were 90.9% (30/33) for Neisseria gonorrhoeae, 91.5% (43/47) for Chlamydia trachomatis, 71.4% (5/7) for Mycoplasma genitalium, and 100% (13/13) for Ureaplasma urealyticum. The main adverse event was diarrhea and its manifestation rate was 35.2% (32 of 120). The symptom of diarrhea was mostly temporary and resolved spontaneously. The conclusion was that the treatment regimen with a single oral 2 g dose of azithromycin extended-release would be effective for patients with urethritis. However, the antimicrobial susceptibilities of Neisseria gonorrhoeae and Mycoplasma genitalium should be carefully monitored because of possible treatment failure.